Enrolled nurse to registered nurse: is there a link between initial educational preparation and course completion? - Rapley, Pat; Davidson, Laura; Nathan, Paula; Dhaliwal, Satvinder (Elsevier, 2008)
Summary There is a shortage of registered nurses (RN) globally and equally in rural areas of Australia. The sparsely populated areas of rural Australia prompted the development of an external-mode EN-to-RN pathway course for enrolled nurses (EN) who want to complete a nursing degree. However, the awarding of advanced standing for EN clinical experience, regardless of educational background, is anew initiative that needs to be evaluated. Hence, this paper reports on the link between initial EN educational preparation and its impact on course completion. This exploratory correlation study used existing course data from four cohorts between 2000 and 2003. The comparisons included educational background, years of experience, and location of the EN-to-RN students. Significant differences were not found between rural and metropolitan students who completed or who withdrew from the course. Logistic regression analysis indicated that ENs in this sample with a hospital-based certificate rather than a technical college qualification were more likely to complete the course: Location and years of experience as an EN did not contribute significantly to course completion.*